657 Right ventricle systolic function and RV-PA coupling in patients with severe aortic stenosis and the early impact of TAVI. (8th December 2021) - Lillo, Rosa; Graziani, Francesca; Ingrasciotta, Gessica; Przbybylek, Bianca; Iannaccone, Giulia; Locorotondo, Gabriella; Pedicino, Daniela; Aurigemma, Cristina; Romagnoli, Enrico; Trani, Carlo; Lanza, Gaetano Antonio; Lombardo, Antonella; et al.
Abstract: Aims: Few data are available on the prevalence of right ventricle (RV) systolic dysfunction, assessed including RV strain, and RV to pulmonary artery (PA) coupling in patients with aortic stenosis (AS) submitted to TAVI and the early effect of the procedure. Methods: We performed standard and speckle tracking echocardiography in 80 patients with severe AS the day before TAVI and within 48 h after TAVI. In all patients we measured TAPSE/PASP (cut-off for RV-PA uncoupling 0.31) and in 60/80 we were able to analyse RV global longitudinal strain (RV-GLS) and RV free wall strain (RV-FWS). Results: RV-FAC and TAPSE were impaired in 8.3% while RV-GLS and RV-FWS in 45% and 33% before TAVI. TAPSE/PASP<0.31 was documented in 7/80 patients (8.7%) before TAVI. These subjects differed from patients with TAPSE/PASP>0.31 for: enlarged left ventricular (LV) end-diastolic and end-systolic volumes ( P <0.001), worst LVEF ( P <0.001) and RVFAC ( P <0.001), worst RV-GLS and RW-FWS ( P =0.01 and P =0.03) and bigger right atrium (RA) area ( P <0.001). After TAVI, RV systolic function did not improve while PASP significantly decreased ( P =0.005) driving the improvement of TAPSE/PASP ( P =0.01). Patients with TAPSE/PASP improvement (51%) differed from the others for worst pre-TAVI diastolic function (E/e' P =0.045), RV-FAC ( P =0.042), RV-GLS ( P =0.049) and RA area ( P =0.02). Conclusions: RV-GLS unveils RV systolic dysfunction in as much as 45% of patients with AS vs. only 8.3% revealed by conventional echocardiography. RV systolic function does not significantly improve early after TAVI while RV-PA coupling does. Patients with lower TAPSE/PASP at baseline have worst LV and RV systolic function as well as larger RA. Patients who improve TAPSE/PASP after TAVI are those with worst diastolic function, RV systolic function and larger RA at baseline.